Correlations for heat transfer characteristics of the onset of nucleate boiling in submerged jet impingement - Fan, Simiao (2022)
The submerged jet impingement boiling is one of the most effective heat transfer methods in dissipating both transient and steady concentrated heat loads. However, studies on the submerged jet impingement boiling still lack experimental data, especially for the heat transfer characteristics of the onset of nucleate boiling (ONB). Therefore, an experimental study of a submerged circular jet impinging on a polished copper surface is conducted in the subcooled water. The experiments investigate the steady-state heat transfer characteristics at the stagnation point from single phase convection to partial nucleate boiling. The effects of jet Reynolds number, liquid subcooling, and nozzle diameter on the onset of nucleate boiling are systematically studied. The experimental results show that the single phase convective heat transfer can be enhanced by increasing jet velocity at a fixed nozzle diameter or decreasing nozzle diameter under the same jet Reynolds number. The liquid subcooling seems to have negligible effect on the single phase heat transfer coefficient. For the ONB point, it is found that the ONB wall superheat is not influenced by liquid subcooling or jet parameters. The ONB heat flux, on the other hand, is found to depend on the experimental parameters. Increasing the jet Reynolds number and liquid subcooling, or decreasing the nozzle diameter could broaden the single phase convective regime and delay the onset of nucleate boiling, in terms of heat flux. Empirical correlations are proposed for predicting the stagnation point heat transfer coefficient, heat flux, and wall superheat at the ONB point. The comparison between the predicted values and the experimental data indicates that the empirical correlations are able to predict the heat transfer characteristics of the onset of nucleate boiling within an acceptable accuracy under the applicable range.